Introduction to Printed Electronics - Suganuma, Katsuaki; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This book describes in detail modern technologies for printed electronics, explaining how nanotechnology and modern printing technology are merging to revolutionize electronics fabrication of thin, lightweight, large, and inexpensive products. Readers will benefit from the explanations of materials, devices and circuits used to design and implement the latest applications of printed electronics, such as thin flexible OLED displays, organic solar cells, OLED lighting, smart wallpaper, sensors, logic, memory and more.
Introduction -- Printing technology -- Conduction materials for PE -- Semiconductor materials -- Substrate and barrier film -- Interconnection -- Next step.
Keywords: Engineering; Electronics; Systems engineering; Engineering; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Electronic Circuits and Devices